Growth and rupture of an intracranial aneurysm: the role of wall aneurysmal enhancement and CD68 - Cannizzaro, Delia; Zaed, Ismail; Olei, Simone; Fernandes, Bethania; Peschillo, Simone; Milani, Davide; Cardia, Andrea (Frontiers in surgery, 2023)
Intracranial aneurysms occur in 3%-5% of the general population. While the precise biological mechanisms underlying the formation, growth, and sudden rupture of intracranial aneurysms remain partially unknown, recent research has shed light on the potential role of inflammation in aneurysm development and rupture. In addition, there are ongoing investigations exploring the feasibility of employing new drug therapies for controlling the risk factors associated with aneurysms. CD68, a glycosylated glycoprotein and the human homolog of macrosialin, is prominently expressed in monocyte/macrophages within inflamed tissues and has shown potential application in oncology. An observational study was conducted with the aim of comparing the histological characteristics of aneurysm walls with preoperative MRI scans, specifically focusing on CD68 activity.IntroductionIntracranial aneurysms occur in 3%-5% of the general population. While the precise biological mechanisms underlying the formation, growth, and sudden rupture of intracranial aneurysms remain partially unknown, recent research has shed light on the potential role of inflammation in aneurysm development and rupture. In addition, there are ongoing investigations exploring the feasibility of employing new drug therapies for controlling the risk factors associated with aneurysms. CD68, a glycosylated glycoprotein and the human homolog of macrosialin, is prominently expressed in monocyte/macrophages within inflamed tissues and has shown potential application in oncology. An observational study was conducted with the aim of comparing the histological characteristics of aneurysm walls with preoperative MRI scans, specifically focusing on CD68 activity.An observational pilot study was conducted to investigate the histological characteristics of the aneurysm wall that could be potentially associated with aneurysm growth and rupture. A total of 22 patients diagnosed with ruptured and unruptured intracranial aneurysms who had undergone conventional clipping between January 2017 and December 2022 were included in the study.MethodAn observational pilot study was conducted to investigate the histological characteristics of the aneurysm wall that could be potentially associated with aneurysm growth and rupture. A total of 22 patients diagnosed with ruptured and unruptured intracranial aneurysms who had undergone conventional clipping between January 2017 and December 2022 were included in the study.A histopathological analysis of the aneurysm wall was performed in all patients, particularly focusing on the presence of CD68. A preoperative MRI with gadolinium was conducted in 10 patients with unruptured aneurysms and six patients with ruptured aneurysms. An emergency clipping was performed in the remaining six patients. The results showed that CD68 positivity and wall enhancement were significantly associated with intracranial aneurysm wall degeneration, growth, and rupture.ResultsA histopathological analysis of the aneurysm wall was performed in all patients, particularly focusing on the presence of CD68. A preoperative MRI with gadolinium was conducted in 10 patients with unruptured aneurysms and six patients with ruptured aneurysms. An emergency clipping was performed in the remaining six patients. The results showed that CD68 positivity and wall enhancement were significantly associated with intracranial aneurysm wall degeneration, growth, and rupture.The histological and radiological inflammatory findings observed in the wall of cerebral aneurysms, as well as the CD68 positivity, are significantly associated with the risk of intracranial aneurysm growth and rupture. This study highlights the crucial importance of considering clinical and medical data when making treatment decisions for intracranial aneurysms. Furthermore, it emphasizes the relevance of evaluating wall enhancement in MRI scans as part of the diagnostic and prognostic process.ConclusionThe histological and radiological inflammatory findings observed in the wall of cerebral aneurysms, as well as the CD68 positivity, are significantly associated with the risk of intracranial aneurysm growth and rupture. This study highlights the crucial importance of considering clinical and medical data when making treatment decisions for intracranial aneurysms. Furthermore, it emphasizes the relevance of evaluating wall enhancement in MRI scans as part of the diagnostic and prognostic process.